Implementation of a simple innovative system for postprescription antibiotic review based on computerized tools with shared access. Issue 3 (March 2017) - Bouchand, F.; Dinh, A.; Roux, A.L.; Davido, B.; Michelon, H.; Lepainteur, M.; Legendre, B.; El Sayed, F.; Pierre, I.; Salomon, J.; Lawrence, C.; Perronne, C.; et al.
Summary: Background: Controlling antibiotic use in healthcare establishments limits their consumption and the emergence of bacterial resistance. Aim: To evaluate the efficiency of an innovative antibiotic stewardship strategy implemented over three years in a university hospital. Methods: An antimicrobial multi-disciplinary team (AMT) [pharmacist, microbiologist and infectious disease specialist (IDS)] conducted a postprescription review. Specific coding of targeted antibiotics (including broad-spectrum β-lactams, glycopeptides, lipopeptides, fluoroquinolones and carbapenems) in the computerized physician order entry allowed recording of all new prescriptions. The data [patient, antibiotic(s), prescription start date, etc.] were registered on an AMT spreadsheet with shared access, where the microbiologist's opinion on the drug choice, based on available microbiology results, was entered. When the microbiologist and pharmacist did not approve the antibiotic prescribed, a same-day alert was generated and sent to the IDS. That alert led the IDS to re-evaluate the treatment. Findings: From 2012 to 2014, 2106 targeted antibiotic prescriptions were reviewed. Among them, 389 (18.5%) generated an alert and 293 (13.9%) were re-evaluated by the IDS. Recommendations (mostly de-escalation or discontinuation) were necessary for 136 (46.4%) and the prescribers' acceptance rate was 97%. The estimated intervention time was <30 min/day for each AMT member. This system allowed correct use of targeted antibiotics for 91.8% of prescriptions, but had no significant impact on targeted antibiotic consumption. Conclusion: This computerized, shared access, antibiotic stewardship strategy seems to be time saving, and effectively limited misuse of broad-spectrum antibiotics.